Lyn Phosphorylates and Controls ROR1 Surface Dynamics During Chemotaxis of CLL Cells - Dave, Zankruti; Vondálová Blanářová, Olga; Čada, Štěpán; Janovská, Pavlína; Zezula, Nikodém; Běhal, Martin; Hanáková, Kateřina; Ganji, Sri Ranjani; Krejci, Pavel; Gömöryová, Kristína; Peschelová, Helena; Šmída, Michal; et al. (Frontiers in Cell and Developmental Biology, 2022)
Chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL) are malignancies characterized by the dependence on B-cell receptor (BCR) signaling and by the high expression of ROR1, the cell surface receptor for Wnt-5a. Both, BCR and ROR1 are therapeutic targets in these diseases and the understanding of their mutual cross talk is thus of direct therapeutic relevance. In this study we analyzed the role of Lyn, a kinase from the Src family participating in BCR, as a mediator of the BCR-ROR1 crosstalk. We confirm the functional interaction between Lyn and ROR1 and demonstrate that Lyn kinase efficiently phosphorylates ROR1 in its kinase domain and aids the recruitment of the E3 ligase c-CBL. We show that ROR1 surface dynamics in migrating primary CLL cells as well as and chemotactic properties of CLL cells were inhibited Lyn inhibitor dasatinib. Our data establish Lyn-mediated phosphorylation of ROR1 as a point of crosstalk between BCR and ROR1 signaling pathways.